“Viola sound safari”: Engaging refugee children in extended viola technique for timbre effects through musical game - Wong Siew Ngan; Lee Chie Tsang Isaiah (Scopus, 2024)
Contemporary extended viola techniques have long posed challenges for classically trained violists. Existing research predominantly focuses on expanding the range of new sounds achievable through extended viola techniques, employing instructional and conventional sound experimental methods. The “Viola Sound Safari” is a musical game designed to enhance music learners’ motivation and enjoyment in producing diverse timbres and sounds on the viola. The participants used viola techniques, including glissandi, harmonics, and vibratos, in a treasure hunt for specific timbres/sounds. Data collection encompassed focus group and individual semi-structured interviews, observation, and participant feedback surveys. Participants were refugee children (aged 9 – 15) engaged in recreational music learning and playing. This musical game additionally aims to foster social interaction, teamwork, and enjoyable learning within confined spaces of the viola’s timbre and sound production capabilities. Integrating play elements, fun activities, and interactive approaches in enhancing timbre sound productions for viola technique learning, the outcome of this research addresses a positive, effective, and enjoyable experimenting process through musical games for refugee children.